Analisis Profitabilitas Perusahaan Kompas 100 Sebelum dan Saat Pandemi Covid-19 - Sherfina Tabatini Evany; Risal Rinofah; Pristin Prima Sari (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
This study aims to find out how significant the difference caused by the covid-19 pandemic is on the Profitability (ROA,ROE,NPM) of the Kompas 100 company.In this research, using descriptive comparative with quantitative approach and using secondary data. The population includes companies listed on the Kompas 100 index on the Indonesia Stock Exchange, then selected using purposive sampling technique, obtained a total of 46 companies that meet the criteria. The profitability uses (ROA, ROE, NPM). Then the ratio was tested differently using the Wilcoxon sign rank test with the help of SPSS 22.The results showed that there was a significant difference in profitability ratios which included ROA, ROE and NPM at the Kompas 100 company between the period before and during the covid-19 pandemic. Keywords: Profitability, ROA, ROE , NPM